Clinical Characteristics of Patients with a Right Ventricular Thrombus in Arrhythmogenic Right Ventricular Cardiomyopathy - Akdis, Deniz; Chen, Kai; Saguner, Ardan M.; Stämpfli, Simon F.; Chen, Xiao; Chen, Liang; Rao, Man; Haegeli, Laurent M.; Tanner, Felix C.; Brunckhorst, Corinna; Song, Jiangping; Duru, Firat (Thrombosis and Haemostasis, 2019)
Background Thrombus formation within the left ventricle (LV) is a well-known clinical entity and is often associated with underlying myocardial disease, whereas right ventricular (RV) thrombi are rarely observed. This study aimed to investigate the clinical characteristics of patients with arrhythmogenic RV cardiomyopathy (ARVC) who developed an RV thrombus.Methods and Results This study included patients with an RV thrombus from the ARVC databases of the University Heart Center in Zurich, Switzerland, and the Fuwai Hospital in Beijing, China. In total, there were 13 ARVC patients who had an RV thrombus detected. The mean age was 33 ± 15 (range: 11–51) years. Eight patients (62%) were male. The mean Task Force score was 6 ± 1. Nine of these patients (69%) had an RV thrombus only whereas four patients had biventricular thrombi. All 13 ARVC patients had a severely impaired RV function (RV fractional area change 16 ± 9% and RV ejection fraction 15 ± 4%); LV ejection fraction (LVEF) was 40 ± 15%. ARVC patients with an additional LV thrombus had a lower LVEF than the others (24 ± 11 vs. 47 ± 11, p = 0.02). Under therapeutic anticoagulation, complete thrombus resolution was observed in 9/13 patients (69%).Conclusion RV thrombus formation is a potential complication of ARVC with impaired RV function. In patients with biventricular involvement, thrombi may also occur within the LV. Anticoagulation is generally effective to dissolve RV thrombi. This study highlights the need for awareness during cardiac imaging to detect this rare complication of ARVC.
Keywords: right ventricle; thrombus; arrhythmogenic; cardiomyopathy; anticoagulation; imaging